Large-Area Structure-Selective Synthesis of Symmetry-Broken MoSe2 and Their Broadband Nonlinear Optical Response - Ahn, Joohyeon; Ha, Seongju; Choi, Jungseok; Yeom, Dong Il; Yoo, Youngdong (Advanced Optical Materials, 2023)
Transition metal dichalcogenides (TMDCs) have various electronic and optical properties depending on their structure, so they can be used as a fascinating material in various applications including photonics, electronics, optoelectronics, and valleytronics. In particular, spiral TMDCs grown through the formation of screw dislocations exhibit novel electronic and optical properties different from layer-by-layer TMDCs. However, large-area structure-selective synthesis of TMDCs remains challenging. Here, this work reports for the first time the large-area structure-selective synthesis of monolayer MoSe2 and spiral MoSe2 using a flux-controlled chemical vapor deposition method. Under a low MoSe2 flux condition, monolayer MoSe2 is synthesized, whereas thick spiral MoSe2 is synthesized under a high flux condition. Under a medium flux condition, both monolayer and spiral MoSe2 are synthesized. In addition, through the nonlinear optical (NLO) signal analysis of monolayer MoSe2 and spiral MoSe2, the giant enhancement of NLO signals induced by the combined effect of breaking inversion symmetry and the excitonic resonance effects in the synthesized MoSe2 is confirmed. Monolayer MoSe2 and spiral MoSe2 synthesized using this method are expected to be used as advanced optical materials for novel electronics, optoelectronics, and NLO applications.
Keywords: Dichalcogenides; Electronic and optical properties; Flux conditions; Harmonics generation; Large area synthesis; Selective growth; Selective synthesis; Spiral mose2; Structure-selective growth; Synthesised; harmonic generation; large-area synthesis; nonlinear optics; spiral MoSe2; structure-selective growth